PERANCANGAN APLIKASI DOKUMENTASI SEMINAR PARA DOSEN DI STMIK ANTAR BANGSA - Subhiyanto; Aristejo; Esthi Adityarini (LPPM STMIK ANTAR BANGSA, 2023)
At present the need for seminars is mandatory for lecturers as a support in carrying out the Tridharma of higher education and also for updating knowledge that is developing. At STMIK Antar Bangsa, many lecturers often carry out seminar activities, but these activities are still not well documented both in administration and in reports. To overcome this problem, we took the initiative to design a lecturer seminar documentation system application. The method used is RAD (Rapid Application Development) with the aim of accelerating the development of seminar documentation application designs for lecturers with good and quality results.